Аполлон ΙНΤΡΟΣ и Артемида Пифийская. О двух культах милетских апойкий Причерноморья - Шелов-Коведяев, Ф.В. (Материалы по археологии Северного Причерноморья, 2019)
Религиозная жизнь древних – одна из самых сложных, а порой и запутанных, тем в антиковедении. К счастью, знания о ней продолжают постоянно пополняться благодаря материалам, которые поступают из раскопок. The paper presents some graffiti from excavation of Panticapaeum at seasons of 2016–2017 years. The first, ’Απόλ]λων’ ’Ιητ[ρôι | ’Αγή]τορι Äε[λφινίωι, argues the Ju.G. Vinogradov’s hypothesis that Apollo Ietros was called by the common oracle issued from Didyma as leader of Milesian colonization in Pontus and changed in this part Apollo Delphinios. From other hand, a number of graffiti naming Artemis Pythia brings the sensation – the existence on Bosporus Cimmerian of cults of Artemis Pythia and ipso facto of Apollo Pythios as paredros of Artemis. The last fact accentuates also the leading role of Didyma sanctuary in the colonization process of Pontus. Besides the Semitic background of Apollo’s Ietros cult and his development from the fetish in front of gate/door in Asia Minor to custodian of passage into Hades on northern Black Sea shore are discussed.